PD-1 expression and its significance in tumour microenvironment of hepatocellular carcinoma - Tan, Kai Wei; Chacko, Ann-Marie; Chew, Valerie (Translational Gastroenterology and Hepatology, 2019)
Hepatocellular carcinoma (HCC), the most common manifestation of primary liver cancer, is the fifth most common cancer, and the third leading cause of cancer mortality worldwide (1,2). Depending on the stage of the tumour and liver status, HCC is traditionally treated either with surgery (e.g., surgical resection; liver transplantation), localized therapy (i.e., embolization, either chemically or radiologically) or systemic treatment (e.g., tyrosine kinase inhibitor) (3). Among all these methods, only liver transplantation is considered the most effective treatment. However, due to the shortfall in cadaveric or living-donor organs, liver transplantation is limited to patients with early-stage HCC, and only after fulfilling stringent inclusion criteria, such as the Milan criteria.